The assessment of the employment relationship by civil servants: Theoretical and empirical insights from a study in district courts in Lower Saxony - Albert Martin; Marcus Falke; Christian Gade (Management Revue, 2007)
Civil servants in Germany are commonly considered to have special privileges particularly with regard to their employment conditions. This belief is based on the fact that German civil servants ('Beamte') cannot be discharged, which is an aspect of their employment relationship that attracts attention especially in times when the state of the economy is weak. But does security of employment actually play such an important role in the consciousness of employees? Is security of employment really an outstanding determinant of work behaviour or only one factor amongst many others? And: compared to other employees and due to the security of employment civil servants enjoy, do they assess their work situation and their employment relationship differently? In this article we deal with these as well as some further questions. To explain the attitudes towards the employment relationship we present a general model and discuss how the attributes of different types of employment can be incorporated in this model. Theoretical considerations will play a major role in our article. We take this focus deliberately, because the analysis of empirical results demands theoretical interpretation, and because we want to make a contribution to theory development. Our empirical study is based on surveys in eight district courts in Lower Saxony, in twentysix small and medium sized enterprises and on data from the German Socio-Economic Panel.
Keywords: 650; employment relationship; civil servants; courts; working conditions; job satisfaction; theory of organizational behaviour; Arbeitsverhältnis; Beamte; Gerichtsbarkeit; Arbeitsbedingungen; Arbeitszufriedenheit; Verhalten in Organisationen; Niedersachsen